Anthropology - Ember, Carol R (Prentice-Hall, 1993)
The book introduces to anthropology in general. Then, the book discusses evolutionary theory as it applies to all forms of life; describes the nonhuman primates now living and their variable adaptation; discusses the relative dating of specimens on the basis of stratigraphy and biostratigraphy; the first bipedal homonids, the australopithecines; the transition between Homo erectus and Hom sapiens; the human biological evolution into the present, dealing with biological variation in living human populations; deals with the emergence of broadspectrum collecting and settle life, and the domestication of plants and animals, in various parts of the world; discusses the rise of civilization in a number of areas of the world and the various theories that have been offered to explain the development of statetype political systems; the concept of culture; the various kinds of the oretical orientation or approach in cultural anthropology, in more or less historical sequence; explanation and evidence in cultural anthropology; deals with language and culture, economic systems, social stratification, and political life; discusses the sex differences and sexual behavior, variation in marriage and family; kindship terminology, dealing with the Inuit (Eskimo) system; the women's society called Sande in West Africa; the sphere of life; psychological differences between and within societies, and psychological similarities across societies; the trances, shamanism, ergot poisoning and hallucinations; finally, in chapter "Explaining and Solving Social Problem", this book fucuses on AIDS, diasters, homelessness, crime, family violence, and war